2023
DOI: 10.3390/nu15183863
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Prenatal Vitamin D on Enamel Defects and Tooth Erosion: A Systematic Review

Gianina Tapalaga,
Bogdan Andrei Bumbu,
Sandhya Rani Reddy
et al.

Abstract: Prenatal Vitamin D has been suggested to be critical for dental health in children, affecting outcomes including the prevalence of enamel defects and tooth erosion. This systematic review aimed to evaluate the potential impact of prenatal Vitamin D levels on these dental health outcomes. A total of seven studies, involving 6978 participants, were included after a comprehensive search of PubMed, Web of Science, and Scopus from 2013 to June 2023. The average age of mothers varied across studies, with Vitamin D l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…According to our knowledge, there needs to be a clear, Comprehensive agreement on the role of PVDD with DCs in children, and conflicting results have been reported. A systematic review study has shown that deficiency of micronutrients and vitamins, especially vitamin D, is associated with oral health, tooth enamel defects, and tooth erosion in children [ 39 , 40 ]. However, based on our knowledge, a comprehensive meta-analysis study has not investigated the relationship of prenatal vitamin D level with the risk of DCs in children based on various factors, including prenatal vitamin D level, gestational age, and children’s age.…”
Section: Discussionmentioning
confidence: 99%
“…According to our knowledge, there needs to be a clear, Comprehensive agreement on the role of PVDD with DCs in children, and conflicting results have been reported. A systematic review study has shown that deficiency of micronutrients and vitamins, especially vitamin D, is associated with oral health, tooth enamel defects, and tooth erosion in children [ 39 , 40 ]. However, based on our knowledge, a comprehensive meta-analysis study has not investigated the relationship of prenatal vitamin D level with the risk of DCs in children based on various factors, including prenatal vitamin D level, gestational age, and children’s age.…”
Section: Discussionmentioning
confidence: 99%